Konsep Dakwah Islam Berguru dalam Hukum Adat Gayo Bagi Masyarakat Suku Gayo Aceh Tengah - Amrizal Amrizal; Seri Mughni Sulubara (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The purpose of this research is to find out the values contained in the gayo community's berguru event and the content of the da'wah to be conveyed in the berguru event in customary law for the gayo community. The research method used is descriptive research with a leatherative approach. The values contained in the gayo community's berguru event are the value of aqidah education, meaning that in the berguru event, the bride and groom are taught that aqidah in the household is very important, so that the purpose of husband and wife in marriage can be achieved to get benefits and perfectly become an ideal family from the marriage. The value of worship education means that in the berguru event, the bride and groom are taught that Islam prescribes marriage to form a family as a means to achieve happiness in life. The value of moral education is that gayo customs attach great importance to good morals (noble morals). The content of da'wah in berguru is to give advice and remind the values and principles of Islamic teachings to the prospective bride and groom by the imam of each village. The most important da'wah content is to provide lessons on creed, worship and shari'ah as well as physical and spiritual needs.